EVALUATION OF CYTOTOXIC ACTIVITY OF ETHYL ACETATE EXTRACT OF PIGMENT FROM PSEUDOMONAS AERUGINOSA - R KAMBLE, GEETANJALI; SV, HIREMATH; MB, HIREMATH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Bacterial pigments have promising applications in food, cosmetics, textile, and therapeutics. Pigments from microbial origin are stable, safer, cost effective, easy production, and extraction and thus preferred over other natural sources. Under this backdrop, isolation and characterization of pigment-producing bacteria and analysis of bioactivity of the pigment were the aim of the study. From the literature studies, the pigment production was found to be influenced by various physical factors which directed the study toward optimization of physical parameters for pigment production. Methods: Isolation of pigment-producing bacteria from water sample, cultural, and microscopic identification was done as per the standard protocol. Extraction of pigment by solvent extraction was carried out and its antibacterial and cytotoxic activity was assayed. Results: Molecular characterization of the bacteria resembled the query sequence of the isolate to 99% with Pseudomonas aeruginosa strain. Extraction of pigment by solvent extraction method resulted in crude pigment extract with antibacterial activity against Gram-negative bacteria (17 mm zone of inhibition) at 100 μg/ml concentration. Pigment showed dose-dependent inhibition on proliferation of HeLa cells at the concentration of 345.83 μg/mL. Conclusion: From the above results, it was evident that the pigment extracted from the bacterial isolate Pseudomonas aeruginosa strain JBT18N was therapeutically potential.